Theory of international trade : a dual, general equilibrium approach - Dixit, Avinash K. (Cambridge economic handbooks., 1980)
This book expounds trade theory emphasizing that a trading equilibrium is general rather than partial, and is often best modelled using dual or envelope functions. This yields a compact treatment of standard theory, clarifies some errors and confusions, and produces some new departures. In particular, the book (i) gives unified treatments of comparative statics and welfare, (ii) sheds new light on the factor-price equalization issue, (iii) treats the modern specific-factor model in parallel with the usual Heckscher-Ohlin one, (iv) analyses the balance of payments in general equilibrium with flexible and fixed prices, (v) studies imperfect competition and intra-industry trade.